Perkembangan Anak Usia Dasar Dalam perspektif Islam Melalui Keluarga: Perkembangan Anak Usia Dasar Dalam perspektif Islam Melalui Keluarga - Pratiwi Husain , Alma (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Growth and development in humans are, in a process, always related but have different meanings. Growth is related to changes that can be measured, whereas development is the more perfect the systems work in the body. Islam discusses various forms of study that concern all phenomena of human life, one of which is related to children in their growth and development. The formulation of the problem in this study is focused on the growth and development of elementary age children in an Islamic perspective. This study uses a qualitative approach with library research methods. The results of the study describe the related concepts of basic age children, children in an Islamic perspective, basic age child development, child development in an Islamic perspective, family parenting in child development, family education patterns in an Islamic perspective. Parenting patterns in the family can affect the child's development. So that providing the correct initial parenting style is needed, one of which is by providing a planned education pattern. Parenting patterns and children's education patterns must run dynamically in accordance with the development of children's lives, especially at elementary age